2011
DOI: 10.1016/j.prro.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Palliative thoracic radiotherapy in lung cancer: An American Society for Radiation Oncology evidence-based clinical practice guideline

Abstract: PurposeTo provide guidance to physicians and patients with regard to the use of external beam radiotherapy, endobronchial brachytherapy, and concurrent chemotherapy in the setting of palliative thoracic treatment for lung cancer, based on available evidence complemented by expert opinion.Methods and MaterialsA Task Force authorized by the American Society for Radiation Oncology (ASTRO) Board of Directors synthesized and assessed evidence from 3 systematic reviews on the following topics: (1) dose fractionation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
124
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 175 publications
(134 citation statements)
references
References 51 publications
4
124
0
6
Order By: Relevance
“…16 Similar guidelines for palliation of thoracic lesions support use of regimens of 10 fractions or fewer for patients with limited life expectancy. 32,33 Quality indicators reflecting these recommended palliative radiation dosing schedules could be derived from these guidelines, which would offer metrics for future study of palliative radiotherapy practice. Future administrative data research efforts could be aided by incorporation of diagnosis and claims codes that specifically included codes for anatomic sites of metastases as well as palliative radiotherapy procedures (eg, whole-brain radiation therapy) in the International Classification of Disease-10 and Common Procedural Terminology code repertoires.…”
Section: ‫ء‬mentioning
confidence: 99%
“…16 Similar guidelines for palliation of thoracic lesions support use of regimens of 10 fractions or fewer for patients with limited life expectancy. 32,33 Quality indicators reflecting these recommended palliative radiation dosing schedules could be derived from these guidelines, which would offer metrics for future study of palliative radiotherapy practice. Future administrative data research efforts could be aided by incorporation of diagnosis and claims codes that specifically included codes for anatomic sites of metastases as well as palliative radiotherapy procedures (eg, whole-brain radiation therapy) in the International Classification of Disease-10 and Common Procedural Terminology code repertoires.…”
Section: ‫ء‬mentioning
confidence: 99%
“…[38][39][40][41][42] Although such guidelines have the potential to improve radiation oncology practice by better educating practitioners, our observation that practice may vary according to reimbursement structure suggests that realignment of financial incentives for treatment may also be warranted.…”
Section: -7mentioning
confidence: 99%
“…The authors found that there was a greater likelihood of symptom improvement and a modest benefit in overall survival with radiotherapy schedules of 35 Gy 10 BED (i.e., 30 Gy in ten fractions) or greater. These findings informed various consensus papers including the American Society for Radiation Oncology (ASTRO) practice guideline [21], and an international consensus statement [22]. The general recommendations from the above reviews and guidelines are that radiotherapy schedules of 35Gy 10 BED (i.e., 30 Gy in ten fractions) or greater should be considered for patients with good performance status.…”
Section: External-beam Radiotherapymentioning
confidence: 84%